Nutrients and bioactive compounds in wild fruits from the Brazilian Amazon rainforest - PAULA FILHO, Galdino; SOUZA, Clarice; LUCIA, Ceres Della; SANT’ANA, Helena; SANTOS, Ricardo Henrique (Food Science and Technology, 2023)
The Amazon Rainforest presents a great diversity of wild fruits that constitute an important part of the diet of many families. The present study investigated the nutritional composition of pequiá (Caryocar villosum (Aubl.)), camapu (Physalis angulata L.), tucumã (Astrocaryum vulgare Mart.), uxi (Endopleura uchi (Huber.)), and bacaba (Oenocarpus bacaba Mart.). Gravimetric methods were used to determine moisture and ash after drying in an oven and a muffle furnace, respectively. Total phenolics by Folin-Ciocalteu method, carotenoids by HPLC-DAD, and minerals by atomic absorption spectrophotometry were used. C. villosum obtained the highest concentration of carbohydrates and K; P. angulata showed the highest concentration of Mg; A. vulgare obtained the highest concentration of dietary fiber and carotenoids; E. uchi had the highest concentration of Ca and the highest total energy value; and O. bacaba showed the highest concentration of proteins, P, and total phenolics. It was observed that the species A. vulgare presented the highest concentrations of the main nutrients analyzed; carbohydrates manifested in greater quantity in the species C. villosum, while phenolics were in the species A. vulgare and O. bacaba. The nutritional values found in these fruits are superior to those of other species consumed in Brazil, especially those arising from genetically improved crops.